Repetition in Surah al-Fath: (Qur’anic Stylistic Studies) - Hanik Mahliatussikah; Himatul Istiqomah (AJIS: Academic Journal of Islamic Studies, 2020)
Language and literature have a complex relationship with religion. The concrete example of these relationship can be observed in the Qur’an. The Qur’an as a Muslim holy book is revealed in Arabic which is fulled by beautiful language styles. Even, the beauty of diction in the Qur’an was recognized by prominent Arabic literaturer in his time. One of language style which dominates the beauty of the Qur’an is repetition. Therefore, the research of repetition in the Qur’an is importance in term of linguistics, literature, and religion. Through a qualitative approach and content analysis, this research aims to explore the types of repetition in one of Madaniyah’s surah, namely al-Fath. The results are found in this surah as follows. 1) There are four types of repetition in surah al-Fath, namely phonological, morphological, syntax, and semantic repetition. 2) The most common repetition found in Surah al-Fath is phonological repetition then syntax repetition. 3) Themost common type of phonological repetition is initial rhyme as morpheme. 4) the most common type of syntax repetition is word repetition as partial reduplication.The results of this research are useful as a theoretical reference, especially regarding the style of repetition in the Qur’an